2018
DOI: 10.1002/pssr.201800124
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Residual Impurities in Homoepitaxial m‐Plane GaN by Using N2 Carrier Gas in Metalorganic Vapor Phase Epitaxy

Abstract: The reduction of unintentional impurities in m-plane 10 10Þð GaN homoepitaxial layers is demonstrated by using nitrogen (N 2 ), as opposed to hydrogen (H 2 ), as carrier gas in metalorganic vapor phase epitaxy (MOVPE). Secondary ion mass spectrometry (SIMS) analysis shows that the impurity levels of residual oxygen (O), carbon (C), and silicon (Si) are decreased by nearly one order of magnitude in N 2 -grown samples. Although the full width at half maximum (FWHM) values for the on-axis m-plane X-ray rocking cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Barry et al have recently reported the presence of a heavily undulated surface in the planar homoepitaxial growth of m -plane GaN using a H 2 carrier gas, whereas, growth in a N 2 carrier gas promoted the formation of atomically flat surface resulting in m -plane GaN with reduced oxygen, carbon, and silicon impurities. 33 Earlier work on using pure N 2 as a carrier gas have also demonstrated significantly improved homogeneity, layer purity, and crystal quality in Al-containing ternary AlGaAs alloys, 34 and superior optical properties in a planar AlN epitaxial layer. 35 Similar to our growth of GaN nanowires in the presence of H 2 followed by AlGaN grown in a pure N 2 carrier gas, Yamaguchi et al reported a planar GaN grown in a H 2 carrier gas followed by a GaN/Al 0.17 Ga 0.83 N MQW grown in a N 2 carrier gas which had had superior crystalline and optical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Barry et al have recently reported the presence of a heavily undulated surface in the planar homoepitaxial growth of m -plane GaN using a H 2 carrier gas, whereas, growth in a N 2 carrier gas promoted the formation of atomically flat surface resulting in m -plane GaN with reduced oxygen, carbon, and silicon impurities. 33 Earlier work on using pure N 2 as a carrier gas have also demonstrated significantly improved homogeneity, layer purity, and crystal quality in Al-containing ternary AlGaAs alloys, 34 and superior optical properties in a planar AlN epitaxial layer. 35 Similar to our growth of GaN nanowires in the presence of H 2 followed by AlGaN grown in a pure N 2 carrier gas, Yamaguchi et al reported a planar GaN grown in a H 2 carrier gas followed by a GaN/Al 0.17 Ga 0.83 N MQW grown in a N 2 carrier gas which had had superior crystalline and optical properties.…”
Section: Resultsmentioning
confidence: 99%